Ependymomas arising outside of the central nervous system: A case series and literature review. (January 2018) - Yust Katz, Shlomit; Cachia, David; Kamiya-Matsuoka, Carlos; Olar, Adriana; Theeler, Brett; Penas Prado, Marta; Gilbert, Mark R.; Armstrong, Terri
Highlights: Extra CNS ependymomas are rare tumors, here we present eight patients with extra CNS ependymoma. 5 cases originated in the sacrum or sacral area, and the rest in the breast, lung and the uterus. By histology, most cases were myxopapillary ependymomas (5 cases). Metastases occurred in 6 cases and 3 patients died due to progressive disease. Most cases required surgery, radiation and chemotherapy. Abstract: Background: Extracranial and extraspinal ependymomas are extremely rare tumors mostly published in the literature as case reports. Methods: MD Anderson Cancer Center institutional database was screened for patients with extra CNS ependymomas over a 25 year period. Results: Eight patients with extra CNS ependymoma were identified. Five cases originated in the sacrum or subcutaneous sacral area, and the other 3 cases originating in the breast, lung and adnexa of the uterus. By histology, most cases were myxopapillary ependymomas (5 cases), 2 cases were grade II ependymoma and 1 case was an anaplastic ependymoma. Metastases occurred in 6 cases and 3 patients died due to progressive disease. Most cases required surgery, radiation and chemotherapy. Conclusion: Extra CNS ependymomas are very rare tumors that tend to metastasize, even though most cases are histologically classified as low grade ependymomas.